2021
DOI: 10.3390/biomedicines9091134
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Characterization of EGFP-Labeled Rabbit Limbal Mesenchymal Stem Cells and Their Potential for Research in Regenerative Ophthalmology

Abstract: The development of cell-based approaches to the treatment of various cornea pathologies, including limbal stem cell deficiency (LSCD), is an area of current interest in regenerative biomedicine. In this context, the shortage of donor material is urgent, and limbal mesenchymal stem cells (L-MSCs) may become a promising cell source for the development of these novel approaches, being established mainly within the rabbit model. In this study, we obtained and characterized rabbit L-MSCs and modified them with lent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…CK12 expression is restricted to the corneal epithelium. 80 Antibody staining for vimentin revealed long straight fibrils in mesenchymal cells, while vimentin was found as a dense network of thin fibres in epithelial differentiation, 81 as observed in our study. Most HCECs on the hydrogel membranes and TCPS groups were positive for putative stem cell marker CK19 as well as differentiation cell markers (CK3 and CK12); also, some cells expressed ABCG2 (putative limbal epithelial stem cells), specific patterned expression of vimentin (epithelial differentiation marker), according to immunocytochemistry analysis (corneal and limbal supra‐basal epithelial cells marker).…”
Section: Resultssupporting
confidence: 87%
“…CK12 expression is restricted to the corneal epithelium. 80 Antibody staining for vimentin revealed long straight fibrils in mesenchymal cells, while vimentin was found as a dense network of thin fibres in epithelial differentiation, 81 as observed in our study. Most HCECs on the hydrogel membranes and TCPS groups were positive for putative stem cell marker CK19 as well as differentiation cell markers (CK3 and CK12); also, some cells expressed ABCG2 (putative limbal epithelial stem cells), specific patterned expression of vimentin (epithelial differentiation marker), according to immunocytochemistry analysis (corneal and limbal supra‐basal epithelial cells marker).…”
Section: Resultssupporting
confidence: 87%
“…Mesenchymal stem cells of different origins are known to be able to express both epithelial and mesenchymal markers cultured under certain conditions and to be induced to differentiate into epithelial way. 39 41 For instance, Ma et al successfully used bone marrow-derived mesenchymal stem cells to restore chemically damaged rat corneas. 42 Thus, the co-expression of epithelial and mesenchymal markers in both cultures of rLMSCs and hLMSCs is consistent with the understanding that mesenchymal stem cells could be induced to differentiate into epithelial way and indicates their potential for corneal epithelial reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that rabbit L-MSCs had a high proliferative potential in vitro, expressed epithelial markers, and could differentiate into epithelial-like cells [ 22 ]. The ability of MSCs of various origins to differentiate in diverse directions has been widely discussed in the literature [ 14 , 17 , 18 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to assess the fate of L-MSCs-EGFP [ 22 ] after transplantation onto a damaged cornea in the LSCD model in rabbits. Cells were transferred as part of a tissue-engineered graft based on dHAM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation